Adoption of electronic commerce amongst small and medium enterprises - Thi, Lip Sam; Ang, Chooi Leng (Universiti Utara Malaysia, 2006)
This paper presents initial phase research results that indicate the adoption of e-commerce applications among Malaysian SMEs from the manufacturing sector.Thruough a review of related research on innovation adoption and diffusion, two dimensional model was developed to depict e-commerce adoption.The results indicate that simple e-commerce apprications would be adopted first before SMEs embarked on more complex e-commerce applications.In terms of extent of usage, it was found that a majority of Malaysian mamfacturing SMEs hove adopted ecommerce applications on a parallel basis while vety few SMEs have substituted e-commerce applications for traditional method- of conducting business.